Fe3O4 Microspheres and Graphene Oxide Encapsulated with Chitosan: A New Platform for Sensitive Determination of Hydroquinone and Catechol. Issue 1 (22nd November 2013) - Lai, Ting; Cai, Weihua; Du, Haijun; Ye, Jianshan
Abstract A novel sensor for sensitive determination of hydroquinone (HQ) and catechol (CC) was proposed using a Fe3O4 microspheres‐graphene oxide (Fe3O4‐GO) composites modified glassy carbon electrode (GCE) which was further encapsulated with chitosan (Chit‐Fe3O4‐GO/GCE). The excellent electrocatalytic performance is probably related to the strong synergistic effect of the composites. The proposed sensor shows a linear response for HQ and CC in wide concentration ranges from 1.5 to 150 µM and 1 to 410 µM, with detection limits (S/N=3) of 20 and 250 nM, respectively. Additionally, the sensor exhibits good selectivity and stability in tap water samples.